A rare nexus: G6PD deficiency's uncommon affiliation with rapidly progressive renal failure through the prism of pigment nephropathy - Thakur, Ayush; Admane, Vandana; Jawandhiya, Pankaj; Bahekar, Shital; Jaiswal, Akshay (International Journal of Research in Medical Sciences, 2024)
Acute kidney injury (AKI) with evidence of hemolysis is associated with tropical infections. However, pigment-induced AKI can happen with relatively uncommon genetic causes of hemolytic anemia, i.e., glucose 6-phosphate deficiency (G6PD). We share our experience of one such patients whose clinical presentation was rapidly progressive glomerulonephritis. On evaluation, she had a history of usage of some drugs and with G6PD estimation revealing deficient status even during the episode while other tests such as Coomb's test and bone marrow biopsy was normal. The kidney biopsy revealed diffuse tubular injury with presence of several coarse granular/pigmented casts in tubular lamina. She was managed with hemodialysis and showed complete recovery. Thus, in tropical countries G6PD deficiency although is not common, should be considered among patients who presented as rapidly progressive renal failure (RPRF) and having history of precipitating factors for G6PD deficiency and a detailed hemolytic work-up needs to be carried out as an important cause of preventable recurrent AKI in tropical countries.